2002
DOI: 10.1046/j.1440-0979.2002.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Using therapeutic community principles to improve the functioning of a high care psychiatric ward in the UK

Abstract: The effects of interventions within a high-care psychiatric ward, based upon the principles of a therapeutic community, were evaluated. Interventions included an enhanced physical environment, improved communication, clear rules and aims, and improved safety procedures. A Ward Atmosphere Scale, an Attitude Scale, and interviews with staff indicated improvements in ward atmosphere and staff attitudes. Ward records showed a substantial reduction in the use of seclusion for aggressive patient behaviour, and a 62%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 13 publications
1
55
0
Order By: Relevance
“…The benefits of interventions are discussed in terms of the specific actions taken to reduce restraint and/or seclusion, but also the subsequent change in attitudes, culture and atmosphere on the wards. This is manifest in descriptions of improved leadership roles and communication within multidisciplinary teams For example, the introduction of therapeutic community principles to a ward reduced the use of seclusion, but also improved staff skills, knowledge, self-esteem and renewed sense of optimism (39). One of the few multi-site studies concluded that a nonrestraint movement incorporating hospital and community advocates coupled with new state regulations on restraint were the reasons for changes in attitude, culture and environment within the hospitals (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of interventions are discussed in terms of the specific actions taken to reduce restraint and/or seclusion, but also the subsequent change in attitudes, culture and atmosphere on the wards. This is manifest in descriptions of improved leadership roles and communication within multidisciplinary teams For example, the introduction of therapeutic community principles to a ward reduced the use of seclusion, but also improved staff skills, knowledge, self-esteem and renewed sense of optimism (39). One of the few multi-site studies concluded that a nonrestraint movement incorporating hospital and community advocates coupled with new state regulations on restraint were the reasons for changes in attitude, culture and environment within the hospitals (30).…”
Section: Discussionmentioning
confidence: 99%
“…As with restraint, almost all the studies which measured seclusion episodes reported favourable outcomes (25,30,39,(43)(44)(45). The same study with a negative outcome for restraint episodes also showed an increase in seclusion (29).…”
Section: Seclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extant literature related to inpatient psychiatric nurses was conducted in Australia and New Zealand (Berg & Hallberg, 2000;Cleary, 2004;Cleary & Edwards, 1999;Delaney, Clearly, Jordan, & Horsfall, 2001;Farrell & Dares, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Happell, Martin, & Pinikahana, 2003;O'Brien & Cole, 2004;Taylor & Barling, 2004), Canada (Robinson, Clements, & Land, 2003), England (Callaghan, 1991;Fagin, Brown, Bartlett, Leary, & Carson, 1995;Fagin et al, 1996;Hall, 2004;Higgins, Hurst, & Wistow, 1999;Mistral, Hall, & McKee, 2002;Sammut, 1997;Sullivan, 1993;Whittington, 2002;Whittington & Wykes, 1992), Norway (Severinsson & Hummelvoll, 2001), Sweden (Severinsson & Hallberg, 1998), Japan (Ito, Eisen, Sederer, Yamada, & Tachimori, 2001), and a combination of two or more of the above countries (Melchior, Bours, Schmitz, & Wittich, 1997;Thomsen, Arnetz, Nolan, Soares, & Dallender, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 99%
“…Staff shortage has been identified as a significant stressor for inpatient psychiatric nurses (Fagin et al, 1995(Fagin et al, , 1996Mistral et al, 2002;Taylor & Barling, 2004). Correlations were found between burnout and problems with staffing levels (Sullivan, 1993).…”
Section: Nurse Practice Environmentmentioning
confidence: 99%